KAJIAN PENAMBAHAN BUBUR KULIT BUAH NAGA SUPER MERAH DAN TEPUNG UBI JALAR PUTIH PADA PEMBUATAN KUKIS YANG MENGANDUNG TEPUNG TEMPE - Ryanza ' Lufrandana; Netti ' Herawati; Yusmarini ' ' (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2016)
The purpose of the study was to obtain the best formulation of super red dragon fruit peel pulp and white sweet potato flour on the nutritional value of cookie-generated and approve the SNI 01-2973-1992. The study used a completely randomized design (CRD) with four treatments and four replications. The treatment in this study were K1 (dragon fruit super red peel pulp 5%, white sweet potato flour 30%), K2 (dragon fruit super red peel pulp 10%, white sweet potato flour 25%), K3 (dragon fruit super red peel pulp 15%, white sweet potato flour 20%) and K4 (dragon fruit super red peel pulp 20%, white sweet potato flour 15%). The result showed that the treatments provides significant effect on moisture content, ash content, protein content, and sensory assessment by hedonic the color attribute, but did notsignificantly affectedon the sensory descriptive assessment. Cookie-best treatment in this study was K1 within 4.395% moisture content, 1.928% ash content and 8.957% protein content. Keywords: Cookies, dragon fruit peel, white sweet potato flour